O uso de ferramentas administrativas na gestão das igrejas - F. M. de Oliveira, Wanderson (Vox Scripturae - Revista Teológica Internacional, 2012)
This work exposes the main administrative tools (planning, organization, direction and control) employed by the organizations in general (public or private companies) and makes a study in the Scriptures, searching examples of these tool’s use and how the same can be utilized as assistance for an efficient and effective church management.
Keywords: Administrative tools; Scripture; Church; Church’s Mission